Electronic Cigarettes Use Characteristics Among Smokers in Indonesia - Susi Ari Kristina (Journal of Global Pharma Technology, 2020)
Background: Vape also known as an electronic cigarette that included a set of battery-operated equipment that smoker used to breathe an aerosol, typically conceiving nicotine, flavorings, and other chemicals, and becoming one of the types of a developed cigarette. This study aims to explore the risks and benefits of using electronic cigarettes and investigate factors affecting smokers' use of electronic cigarettes. Methods: This research was a cross-sectional model for Yogyakarta adults using a validated self-administered questionnaire. The questionnaire is divided into three parts: sociodemographic characteristics, smoking, perception of risk-benefit. Data were descriptively and inferentially analyzed using the Chi-square test to investigate factors affecting risk and benefit perception of smokers using electronic cigarettes. Results: Results showed that 133 (66.5 percent) were vape users, and 67 (33.5 percent) were tobacco smokers. Most tobacco smokers and vape users in Yogyakarta province have a high perception of electronic cigarette risk-benefit. Respondent characteristics (age, last education, smoking status) significantly influenced the benefit perception of electronic cigarettes, and smoking status on respondent characteristics also significantly influenced the risk perception among smokers of electronic cigarettes (p